2011
DOI: 10.1155/2011/696535
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nano-ZnO Particle Suspension on Growth of Mung (Vigna radiata) and Gram (Cicer arietinum) Seedlings Using Plant Agar Method

Abstract: The present study demonstrates an effect of nano-ZnO particles on the growth of plant seedlings of mung (Vigna radiate) and gram (Cicer arietinum). The study was carried out in plant agar media to prevent precipitation of water-insoluble nanoparticles in the test units. Various concentrations of nano-ZnO particles in suspension form were introduced to the agar media, and their effect on the root and shoot growth of the seedlings was examined. The main experimental approach, using correlative light and scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
110
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(122 citation statements)
references
References 13 publications
(13 reference statements)
8
110
1
3
Order By: Relevance
“…Such increment in plant growth is probably due to production of higher concentration of auxin under the influence of ZnO nanoparticles (Prasad et al 2012). Previous study also highlighted on retardation in early growth of chickpea seedlings at high dose of ZnO nanoparticles and low dose of ZnO nanoparticles which is sufficient to achieve positive response (Mahajan et al 2011;Burman et al 2013). Recently, Haghighi et al (2014) reported that up to 200 ppm TiO 2 nanoparticles can improve both root and shoot lengths for Lycopersicon esculentum and Allium cepa.…”
Section: Variation Of Root and Shoot Lengthmentioning
confidence: 96%
“…Such increment in plant growth is probably due to production of higher concentration of auxin under the influence of ZnO nanoparticles (Prasad et al 2012). Previous study also highlighted on retardation in early growth of chickpea seedlings at high dose of ZnO nanoparticles and low dose of ZnO nanoparticles which is sufficient to achieve positive response (Mahajan et al 2011;Burman et al 2013). Recently, Haghighi et al (2014) reported that up to 200 ppm TiO 2 nanoparticles can improve both root and shoot lengths for Lycopersicon esculentum and Allium cepa.…”
Section: Variation Of Root and Shoot Lengthmentioning
confidence: 96%
“…Mahajan et al studied mung and Gram seed using nano-ZnO particle by plate agar method and found that the growth of mung and gram is different at different concentrations. The seedling growth was maximum at 20 ppm for mung and at 1 ppm for gram (Mahajan et al 2011). Wang et al (2012 carried out experiment on wheat and found that MWCNT significantly promote cell elongation and increases dehydrogenase activity.…”
Section: Introductionmentioning
confidence: 94%
“…Over last few years, there have been extensive studies to understand the influence of nanomaterials on the growth of different types of plants (Khodakovskaya et al 2009;Khodakovskaya et al 2013a, b;Lu et al 2002;Cañas et al 2008;Yang et al 2006;Hong et al 2005a, b;Tan et al 2009;Yuan et al 2011;Khodakovskaya et al 2013a, b;Mahajan et al 2011;Wang et al 2012;Larue et al 2012;Miralles et al 2012;Feizi et al 2012;Tripathi et al 2011;Sonkar et al 2012). Khodakovskaya et al (2009Khodakovskaya et al ( , 2013a demonstrated that at very low doses MWCNT can penetrate the seed coat and enhance the germination of tomato plant.…”
Section: Introductionmentioning
confidence: 99%
“…Using the plant agar method, Mahajan et al (2011) observed that ZnO-NPs enhanced growth of mung bean and chickpea (Cicer arietinum) seedlings at low concentrations, for the mung bean seedlings, the best growth response for root (a 42% increase in length or 41% in biomass) and shoot (98% in length or 76% in biomass) was observed at a concentration of 20 mg L −1 over those of the control; for the chickpea seedlings, concentration of 1 mg L −1 caused significant increases in root (53% in length or 37% in biomass) and shoot (6% in length or 27% in biomass) growth as compared to those of the control.…”
Section: Case Studiesmentioning
confidence: 99%